Implementation Strategies to Reduce Gynecological Surgical Site Infections - Hira Saleh, Yahya Khan, Sheeba Khan, Sabah Safdar, Sara Gul, Saweeta Kumari (Pakistan Journal of Medical & Health Sciences, 2022)
Surgical site infection (SSI) is a widespread issue that raises expenditures, duration of hospital visits, readmissions, but also death. This original study objective was to compare the SSI incidence prior to and after the introduction of the BIs as well as to assess the intervention’s effectiveness in decreasing the relative SSI incidence. Method.This study was carried out at Department of Gynecology in Hayatabad Medical Complex, Peshawar, Pakistan from January 2021 to October 2021. Following 30 days following surgery, the prevalence of SSIs was studied. Of the 850 participants with GM who were diagnosed, 630 had laparotomies prior to (PRE) and 220 following (POST) the installation of BI. Result The most frequent suggestion was OC. There was a substantial decrease in the SSI frequency between OC laparotomies, including those without BR (PRE 11% (45/395) vs. POST 4.3% (7/162); RRR 81.7%; OR 0.14, 95% CI 0.06-0.52; p value less than 0.002) also those through BR (Pre 67.3% (31/46) against Post 14.2% (2/14; RRR 86.7%; OR 0.06, 95% CI 0.02–0.57; p = 0.003). the total SSI incidence within UC decreased from 25.8% (47/182) to 15.3% (6/39; RRR 48%; OR 0.46, 95% CI 0.17-1.34; p = 0.133). Overall SSI rates among CC decreased from 17.6% (6/34) to 0 (0/15). Conclusion Most commonly, conventional bundles of implementation interventions are used in SSI prevention. The rate of SSI in GM significantly decreased once BI was implemented. Keywords: Surgical site infection, laparotomies, gynecological cancers, gynecology oncologist.